(untitled) (NTU Journal of Engineering and Technology, 2026)
This research includes a practical investigation on the impacts of adding phase change materials (PCMs) into metal foam made from copper in heat sinks, as well as using metal foam alone during heating and cooling. This study used RT55 paraffin as a phase change material. Five cases were used in the experiments. Each one contained a varied quantity of PCM and copper metal foam, in addition to the centrifugal fan-forced airflow inside the device duct and electrical heating of a plate made of copper under the thermal dissipator. This study looked at the impact of thermal energy and intake air velocity coefficients on five heat sink cases Throughout the process of heating and process of cooling. The findings indicate that in the situation of copper foam (case 3), The copper plate has a lower temperature relative to the other instances. During the heating procedure, cases 5 (Paraffin partly filled copper foam) and 3 (2-piece foams made of copper) showed percentage temperature reductions of 57.46% and 66.4% respectively, when compared to case 1 (Absent paraffin or copper foam). During the process of cooling, the high conductivity for copper foam results in case 3 having temperatures that are 43.5% lower than that of case 5, which is 34.7%. furthermore, raising the input air velocity includes less of an impact on heating reduction in scenarios involving phase change materials (PCMs).